LIVING AROUND COFFEE: SOCIAL MARGINALIZATION OF SMALL PRODUCERS IN SAN PEDRO CAFETITLAN, OAXACA, MEXICO - Morales Becerra, Israel (2013)
This article presents an ethnographic description of the field work carried out in San Pedro Cafetitlan, Oaxaca, Mexico on the social exclusion resulting from the implementation of the neoliberal economic model; an interpretation of the meaning that the cultivation of coffee has in the life of the villagers is given. Highlighted is the fact that generations older than 60 years still value the cultivation, and identity with the land and hold hope for their coffee; however, for the new generations the coffee has ceased to be an important resource because it is not possible to subsist on the crop, which is why many have chosen to sell their lands and migrate. Social disintegration caused by the migration has put at risk the conservation of cultural traditions and customs generated at the beginning of the twentieth century in this community.